Combined 3T Diffusion Tensor Tractography and 1H-MR Spectroscopy in Motor Neuron Disease - Nelles, M.; Block, W.; Träber, F.; Wüllner, U.; Schild, H.H.; Urbach, H. (American Journal of Neuroradiology, 2008)
BACKGROUND AND PURPOSE: Diagnostic confidence in motor neuron disease may be improved by the use of advanced MR imaging techniques. Our aim was to assess the accuracy (sensitivity/specificity) and agreement of combined 1H-MR spectroscopy (proton MR spectroscopy) and diffusion tensor imaging (DTI) at 3T in patients with suspected motor neuron disease regarding detection of upper motor neuron (UMN) dysfunction.MATERIALS AND METHODS: Eighteen patients with suspected motor neuron disease were studied with MR spectroscopy/DTI and clinically rated according to the El-Escorial and ALSFRS-R scales. For MR spectroscopy, absolute N-acetylaspartate (NAA), choline (Cho), and phosphocreatine (PCr) concentrations and relative NAA/Cho and NAA/PCr ratios of corresponding volumes of interest within the primary motor cortex were calculated. For DTI, fractional anisotropy (FA) and mean diffusivity (MD) were measured bilaterally at the level of the precentral gyrus, corona radiata, internal capsule, cerebral peduncles, pons, and pyramid. FA and MD statistics were averaged on the corticospinal tracts (CSTs) as a whole to account for a region-independent analysis.RESULTS: MR spectroscopy indicated NAA reduction beyond the double SD of controls in 6 of 8 patients with clinical evidence for UMN involvement. Congruently, the mean FA of these patients was significantly lower in the upper 3 regions of measurements (P < .01). Overall, MR spectroscopy and DTI were concordant in all except 3 cases: 1 was correctly excluded from motor neuron disease by DTI (genetically proved Kennedy syndrome), whereas MR spectroscopy indicated CST involvement. MR spectroscopy and DTI each were false-positive for CST affection in 1 patient with lower motor neuron involvement only.CONCLUSION: Combined MR spectroscopy/DTI at 3T effectively adds to the detection of motor neuron disease with a high degree of accordance.